P-167 Impact of Neddylation Inhibition on NF-κB and Mucosal Inflammatory Responses. (March 2016) - Curtis, Valerie; Ehrentraut, Stefan; Campbell, Eric; Glover, Louise; Kominsky, Douglas; Colgan, Sean
Abstract : Background: Recent work has identified a central role for neddylation (the conjugation of a Nedd8 protein to Cullin proteins) to the induction of the NF-κB pathway (via Cullin-1) and stabilization of hypoxia-inducible factor (HIF, via Cullin-2) during inflammatory responses. Our recent work revealed that pharmacological stabilization of HIF with the neddylation inhibitor MLN4924 significantly abrogated colitis endpoints in mice. In the present studies, we addressed the contribution of Cullin-1 neddylation and NF-κB signaling to mucosal inflammatory responses in vitro and in vivo. Methods: Initial in vitro studies using western blot analysis and luciferase reporter assays were performed on Caco-2 intestinal epithelial cells. Barrier function of T84 intestinal epithelial cells treated with cytokines and MLN4924 in combination compared to alone as measured by transepithelial resistance (TER) and permeability assays was also assessed. Finally, in vivo administration of MLN4924 (3 mg·kg −1 ·d −1 ) in a TNBS colitis model was performed to evaluate the influence on disease severity. Results: In vitro assays revealed that MLN4924 prominently induces the deneddylation of Cullin-1 and inhibited NF-κB signaling. This inhibition resulted in decreased barrier function as demonstrated by decreased TER and increased permeability after treatment with a combination of MLN4924 and cytokines, but not with MLN4924 alone. In vivo treatment with MLN4924 significantly increased disease severity as measured by increased colon shortening and mortality early in the inflammatory response (day 2). Histologic analysis of the colon revealed that neddylation inhibition results in increased tissue damage and significantly increased mucosal apoptosis as determined by TUNEL and cleaved caspase-3 staining, particularly within the epithelium. Conclusions: These studies reveal that Cullin-1 neddylation, and most particularly NF-κB signaling, is protective during mucosal inflammatory responses. We conclude that Cullin-1 neddylation fine-tunes the mucosal inflammatory response in vitro and in vivo.